IT Frameworks for Hospital Management and Standardization: Benchmarking ITIL, COBIT, and ITSM - Bruno Ocupa, Jose Isabel; Ruesta Velázquez, Rex Harrison; Luis Alberto, Casaverde Pacherrez; Francisco Alonso, Donayre Monteza (LACCEI, 2025)
The following systematic review discusses the effectiveness of ITIL, COBIT, and ITSM frameworks in standardizing IT services in hospital settings. The objective was to compare how these management frameworks contribute to improving incident management, operational continuity and the perception of user quality in health institutions. 36 articles published between 2020 and 2025 were analyzed, selected using the PICOC technique and following the PRISMA methodology. The findings reveal that ITIL is the most adaptable framework in resource-constrained hospitals, achieving a 25% decrease in incident resolution times and a 60% increase in resolved tickets. COBIT showed strengths in governance and auditing, although with low adoption in rural areas due to its technical complexity. ITSM improved user perception, but with challenges in subjective aspects such as empathy. It is concluded that ITIL is the most viable option for contexts with limited infrastructure, while a hybrid integration with COBIT would be suitable for more complex systems. In addition, the need for more representative research in Latin America is highlighted, to more accurately evaluate the implementation of these in different contexts within a hospital center.